Genetics, shared environment, or individual experience? A cross-sectional study of the health status following SARS-CoV-2 infection in monozygotic and dizygotic twins - Rupp, Sophia Kristina; Weimer, Katja; Goebel-Stengel, Miriam; Enck, Paul; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2022)
Background: The clinical presentation of COVID-19 shows a remarkably broad spectrum of symptoms. Although studies with adult twins on SARS-CoV-2 infection are rare so far, the fact that there is a genetic component associated with the highly variable clinical outcomes of COVID-19 has already been highlighted in recent studies investigating potential candidate genes and polymorphisms. This is the first study of adult monozygotic (MZ) and dizygotic (DZ) twins concordantly affected by SARS-CoV-2 infection to estimate variances explained by genetic, shared, and individual environmental components of both somatic and psychological symptoms following SARS-CoV-2 infection. Methods: Data were collected from 10 adult twin pairs (5 MZ, 5 DZ) in which both twins already had a SARS-CoV-2 infection. A self-designed questionnaire, the Barthel Index, and the Multidimensional Fatigue Inventory (MFI) were used to assess various symptoms and health status following SARS-CoV-2 infection. Intra-class correlations were calculated, and the Falconer formula was used to quantify and differentiate the percentages of genetic influences as well as common environment and personal experiences on the examined traits. In addition, potential factors influencing symptom burden were examined and discussed. Results: We found high estimated heritability for mental impairment after SARS-CoV-2 infection (h2 = 1.158) and for general fatigue (h2 = 1.258). For symptom burden, reduced activity, and reduced motivation the individual environment appears to have the strongest influence. Other fatigue symptoms are influenced by genetic effects which range between 42.8% and 69.4%. Conclusion: Both genetics and individual environment play a role in health status after SARS-CoV-2 infection - mental status could be influenced primarily by genetic make-up, whereas for symptom burden and certain fatigue dimensions, non-shared environment could play a more critical role. Possible individual factors influencing the course of the disease were identified. However, gene-environment interactions may still be a source of differences between twins, and the search for candidate genes remains crucial on the road to personalized medicine.